2021
DOI: 10.1111/vox.13056
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pathogen reduction methods on immunological properties of the COVID‐19 convalescent plasma

Abstract: Conclusion Pathogen reduction with methylene blue or with amotosalen provides the greater likelihood of preserving the immunological properties of the COVID-19 convalescent plasma compared to riboflavin.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Methylene blue is a method of pathogen inactivation for plasma that is widely used in some countries in Europe. A study from Russia showed that some units of plasma lost neutralising activity with methylene blue inactivation, 34 whereas other studies found no difference. 35 , 36 We analysed the neutralising activity of stored donor samples (ie, before methylene blue treatment) compared with the plasma unit (ie, after methylene blue treatment) in a subgroup of plasma units and we found no differences in neutralising antibody titres (median ID50 1:1256 [IQR 1:709–1:2712] vs 1:1287 [1:349–1:3333]; p=0·32).…”
Section: Discussionmentioning
confidence: 99%
“…Methylene blue is a method of pathogen inactivation for plasma that is widely used in some countries in Europe. A study from Russia showed that some units of plasma lost neutralising activity with methylene blue inactivation, 34 whereas other studies found no difference. 35 , 36 We analysed the neutralising activity of stored donor samples (ie, before methylene blue treatment) compared with the plasma unit (ie, after methylene blue treatment) in a subgroup of plasma units and we found no differences in neutralising antibody titres (median ID50 1:1256 [IQR 1:709–1:2712] vs 1:1287 [1:349–1:3333]; p=0·32).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that photoinactivation with methylene blue does not significantly reduce the titers of SARS‐CoV‐2 antibodies. 36 , 37 In fact, the methylene blue method has been reported to be less detrimental to anti‐SARS‐CoV2‐2 titers than other pathogen‐reduction technologies currently applied to donated plasma. 36 However, we cannot certainly disregard some decrease in the in vivo neutralizing capacity due to pathogen‐reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples were collected and the analysis of the neutralizing activity of the convalescent blood plasma was carried out in the microneutralization test described earlier [ 22 ]. Live hCoV-19/Russia/Moscow_PMVL-1/2020 virus variant was employed; test was performed as the microneutralization assay with the Vero E6 cells.…”
Section: Methodsmentioning
confidence: 99%